Pengaruh Strategi Pembelajaran dan Kecerdasan Adversiti Terhadap Hasil Belajar Evaluasi Hasil Belajar - Edward Purba (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2015)
The aims of this research is to know in uence the learning strategy and adversity quotient toward the result of study evaluation subject. Research method is quasi experi- mental disign with treatmenby level 2 X 2 and 40 students sampel. Data was collected with achievement test. Research resut indicates that the result of study evaluation subject for students who taught with problem based learning higher than taught with expository. There was interaction between instructional strategies and adversity quotient toward result of study evaluation subject. Concluions the result of study evaluation subject who taught with problem based learning signi cantly higher than taught with expository. There was the interaction between instructional strategies and adversity quotient toward result of study evaluation subject.